Blood pressure-lowering medicines implemented in 12 African countries: the cross-sectional multination EIGHT study - Xavier Jouven; Bamba Gaye; Marie Antignac; Ibrahima Bara Diop; Marie Cécile Perier; Jean Laurent Takombe; Dadhi Balde; Roland N'Guetta; Anastase Dzudie; Liliane Mfeukeu Kuate; Charles Kouam Kouam; Samuel Kingue; et al. (BMJ Open)
Objective In Africa, the number of patients with hypertension is expected to reach 216.8 million by 2030. Large-scale data on antihypertensive medications used in Sub-Saharan Africa (SSA) are scarce.Here, we describe antihypertensive drug strategies and identify treatment factors associated with blood pressure (BP) control in 12 Sub-Saharan countries.Setting Outpatient consultations for hypertension in urban tertiary cardiology centres of 29 hospitals from 17 cities across 12 SSA countries between January 2014 and November 2015.Participants Patients ≥18 years of age with hypertension were enrolled at any visit during outpatient consultations in the cardiology departmentsMain outcome measure We collected BP levels, demographic characteristics and antihypertensive treatment use (including traditional medicine) of patients with hypertension attending outpatient visits. BP control was defined as seated office BP <140/90 mm Hg. We used logistic regression with a random effect on countries to assess factors of BP control.Results Overall, 2198 hypertensive patients were included and a total of 96.6% (n=2123) were on antihypertensive medications. Among treated patients, 653 (30.8%) patients received a monotherapy by calcium channel blocker (n=324, 49.6%), renin–angiotensin system blocker (RAS) (n=126, 19.3%) or diuretic (n=122, 18.7%). Two-drug strategies were prescribed in 927 (43.6%) patients including mainly diuretics and RAS (n=327, 42% of two-drug strategies). Prescriptions of three-drugs or more were used in 543 (25.6%) patients. Overall, among treated patients, 1630 (76.7%) had uncontrolled BP, of whom 462 (28.3%) had BP levels ≥180/110 mm Hg, mainly in those on monotherapy. After adjustment for sociodemographic factors, the use of traditional medicine was the only factor significantly associated with uncontrolled BP (OR 1.72 (1.19 to 2.49) p<0.01).Conclusion Our study provided large-scale data on antihypertensive prescriptions in the African continent. Among patients declared adherent to drugs, poor BP control was significantly associated with the use of traditional medicine.